Cultural determinants of attitudes toward career = Kulturowe uwarunkowania postaw wobec kariery zawodowej - Jaremczuk, Kazimierz; Mazurkiewicz, Anna; Molter, Anna (Zielona Góra: Faculty of Economics and Management Press)
This article is focused on the culture?s influence on the employees' career. The career itself has been interpreted with a particular emphasis on its contemporary understanding. The issue of values internalization has been focused on. To organizational culture?s importance in the career development has been given consideration here - a career in the subjective perspective i.e. identification with a professional group, as well as perceived from both organization?s and the environment's perspective as well. In particular, the problem regards organizational culture as a derivative of the employees' environmental cultures.
Keywords: kariera zawodowa; kultura organizacyjna; nowy typ kariery; career; organizational culture; new type of career